Management of vascular anomalies: Review of institutional management algorithm - Makhija, Lalit K.; Bhattacharya, Sameek (Indian Journal of Plastic Surgery, 2017)
Introduction: Vascular anomalies are congenital lesions broadly categorised into vascular tumour (haemangiomas) and vascular dysmorphogenesis (vascular malformation). The management of these difficult problems has lately been simplified by the biological classification and multidisciplinary approach. To standardise the treatment protocol, an algorithm has been devised. The study aims to validate the algorithm in terms of its utility and presents our experience in managing vascular anomalies. Materials and Methods: The biological classification of Mulliken and Glowacki was followed. A detailed algorithm for management of vascular anomalies has been devised in the department. The protocol is being practiced by us since the past two decades. The data regarding the types of lesions and treatment modality used were maintained. Results and Conclusion: This study was conducted from 2002 to 2012. A total of 784 cases of vascular anomalies were included in the study of which 196 were haemangiomas and 588 were vascular malformations. The algorithmic approach has brought an element of much-needed objectivity in the management of vascular anomalies. This has helped us to define the management of particular lesion considering its pathology, extent and aesthetic and functional consequences of ablation to a certain extent.
Keywords: Algorithm; management; vascular malformation